Pengaruh Model Pembelajaran Kooperatif Jigsaw dan Minat Belajar Siswa terhadap Keterampilan Menulis Teks Iklan Siswa Kelas VIII SMP Negeri 8 Padang - Anna Ratri Novi Lani; Hasnul Fikri; Syofiani Syofiani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This research is motivated by the difficulties faced by students in writing advertising texts at SMP Negeri 8 Padang. This is because teachers do not use varied learning models in the learning process so that students have low learning interest. This study aims to describe the influence of the jigsaw model and learning interest on advertising text writing skills. This type of research is quantitative research with an experimental method. This research was conducted in class VIII of SMP Negeri 8 Padang. The sample of this research was students of class VIII. G as the experimental class and students of class VIII. H as the control class. There are two research instruments, namely a performance test of advertising text writing skills and a questionnaire to measure students' learning interest. Research data collection techniques, namely questionnaires were given to students in the experimental class and the control class. Next, the teacher gave a pretest of advertising text writing skills to see students' initial abilities. The teacher then carried out learning using the jigsaw model in the experimental class and the conventional model in the control class. Next, the teacher gave a posttest of advertising text writing skills to measure students' final abilities. Based on the results of the study, several things can be concluded as follows. First, there is a difference in the results of the argumentative text writing skills test of students using the jigsaw model with the results of the advertising text writing skills test of students using the conventional model with a sig value of 0.000 < 0.05. Second, there is a difference between the results of the advertising text writing skills performance test of students with high learning interest using the jigsaw model with the results of the advertising text writing skills performance test of students with high learning interest using the conventional model with a sig value of 0.000 < 0.05. Third, there is a difference between the results of the advertising text writing skills performance test of students with low learning interest using the jigsaw model with the results of the advertising text writing skills performance test of students with low learning interest using the conventional model with a sig value of 0.003 < 0.05. Fourth, there is no interaction between the problem based learning model and students' learning motivation in influencing the argumentative text writing skills because Fcount (1.403) < Ftable (4.2).